Clinical and angiographic outcomes after stent-assisted coiling of cerebral aneurysms with Enterprise and Neuroform stents: a comparative analysis of the literature. (28th October 2014) - King, Brent; Vaziri, Sasha; Singla, Amit; Fargen, Kyle M; Mocco, J
Abstract : Introduction: The most widely used intracranial stents for stent-assisted coiling are Neuroform (NEU) and Enterprise stents (ENT). This study compares published outcomes between the ENT and NEU coil-assist systems and comments on the published safety and efficacy of stent-assisted coiling in general. Methods: A literature search was performed through PubMed for all published series of ENT or NEU stent-assisted coiling of cerebral aneurysms from 2004 to 2014. All studies including 10 or more published cases of stent-assisted coiling with ENT or NEU were included. Results: 47 studies met the inclusion criteria, containing 4238 aneurysms in 4039 patients. 2111 aneurysms were treated with NEU and 2127 were treated with ENT. Mean follow-up was 14.1 months. Overall, thromboembolic events occurred in 6.4% of aneurysms, intracranial hemorrhage (ICH) in 2.6%, permanent morbidity in 3.9%, and mortality in 2.3%. Initial and final 100% angiographic occlusion was seen in 53% and 69% of patients, respectively. Deployment failures (p<0.001), ICH (p=0.001), mortality among all patients (p=0.03), and recanalization (p=0.02) were more commonly reported in NEU treated aneurysms. The ENT system was also associated with higher reported complete occlusion at follow-up (p<0.001). Conclusions: This literature review represents the largest and most robust comparison of stent-assisted coiling devices to date, containing over 4200 aneurysms in more than 4000 patients. Comparative analyses demonstrate that both devices are reported to be safe and effective with comparable permanent morbidity.